(untitled) (Journal Of Educational and Psychological Researches, 2014)
The current research aims to know the sex-stereotyping among Kindergarten , male and female, study was conducted on a sample of 400 boys and girls by (200) males and (200), females Kindergarten from age (4-6 years) in the province of Baghdad, for the , academic year (2013-2014) In order to achieve the goals of research, the researcher built two scales measure of the prototypical male sexuality and a measure of the prototypical female sexual and be in its final form of (36) items to measure sexual stereotyping male (35) items to measure sexual stereotyping of females, were sure of the validity scale by presentation to a group of experts as well as the Statistical analysis of the researcher to paragraphs as well as finding a relationship paragraph primarily college was to make sure of the vdiability of the scale retail midterm manner and method of coefficient of internal consistency (Cronbach’s alpha), and built the results that the sample has a high level of sexual stereotyping